Penerapan Model Blended Learning dalam Pembelajaran Sejarah di Era Digital pada Kota Ambon - Maysuri, Tama; Kapitanhitu, Reihana; Ima, Wa (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to describe and analyze the implementation of the blended learning model in history education in the digital era, focusing on high schools in Ambon City, Maluku. This study uses a qualitative approach with a case study method. The research subjects consist of a history teacher as the main informant, as well as several eleventh-grade students selected using purposive sampling techniques. Data collection techniques include observation, in-depth interviews, and documentation. The stages of analysis begin with data reduction, data presentation, and conclusion drawing. The research findings indicate that the implementation of blended learning is carried out through a combination of using simple digital platforms such as Google Classroom and WhatsApp for material delivery, along with face-to-face sessions for discussion, clarification, and assessment. Teachers apply learning strategies such as flipped classroom, group discussions, and the utilization of history videos. Students' responses to this model are generally positive as it provides flexibility and increases motivation to learn, although there are technical obstacles such as limited internet access and digital devices. The main challenges in the local context of Ambon include limited infrastructure, uneven digital literacy, and varying levels of learning environment support. This research concludes that blended learning can be an effective solution in enhancing the quality of history education in the digital era, noting the need for policy support and strengthening educational infrastructure in the region.